Facilitating and Regulating Employment - Toogood, Kit (Victoria University of Wellington Law Review, 2002)
This article considers the extent to which Sir Ivor Richardson's Court of Appeal has sought to provide consistency, certainty, and predictability in the development of New Zealand's law regarding redundancy. The author explores important Employment Court and Court of Appeal decisions starting from the employee-friendly Hale case in 1990. The development of redundancy law is then explored through the Brighouse case (which seemingly affirmed Hale), the Davidson saga, and the more employer-friendly Aoraki case (which overruled Brighouse). The article then discusses the future implications of the then-new Employment Relations Act 2000. The result of these developments mean that employees will generally have the right to insist on fair treatment. At the same time, well-advised employers may feel confident that if they follow a considerate process in implementing a redundancy decision, they will not be at risk of having their decisions second-guessed.